التفكير الايجابي وعلاقته بالصحة النفسية لدى تلاميذ الثانية ثانوي دراسة ميدانية بثانوية محمد بن شبيرة-بوسعادة- - حبيش فاطنة; اشراف: ياحي شفيقة (جامعة محمد بوضياف المسيلة, 2025)
ملخص الدراسة: هدفت الدراسة الى التعرف على طبيعة العلاقة بين التفكير الإيجابي والصحة النفسية لدى تلاميذ الثانية ثانوي ، والكشف عن مستوى التفكير الإيجابي ومستوى الصحة النفسية، واستخدمت الباحثة المنهج الوصفي، كما بلغ حجم العينة الأساسية (120) تلميذا وتلميذة في السنة الثانية ثانوي واستخدمت الدراسة مقياس التفكير الإيجابي من إعداد ''وليد أحمد ربيع''(2019)، ومقياس الصحة النفسية'' للقريطي والشخص ''(1998)، و أظهرت الدراسة أن: 1- مستوى التفكير الإيجابي لدى تلاميذ السنة الثانية ثانوي متوسط 2- مستوى الصحة النفسية لدى تلاميذ السنة الثانية ثانوي متوسط 3- توجد علاقة ارتباطية ذات دلالة إحصائية بين التفكير الإيجابي الصحة النفسية لدى تلاميذ الثانية ثانوي. الكلمات المفتاحية: التفكير الإيجابي، الصحة النفسية، تلاميذ المرحلة الثانوية. Study: The study aimed to identify the nature of the relationship between positive thinking and mental health among second-year secondary school students, and to reveal the level of positive thinking and the level of mental health. The researcher used the descriptive approach. The size of the basic sample was (120) male and female students in the second year of secondary school, and the study used the positive thinking scale. Prepared by “Walid Ahmed Rabie” (2019), and the psychological health scale “by Al-Quraiti and the Person” (1998), the study showed that: 1- The level of positive thinking among second-year intermediate secondary students 2- The level of mental health among second-year middle school students 3- There is a statistically significant correlation between positive thinking and mental health among second-year secondary school students. Keywords: positive thinking, mental health, secondary school students.